Zaplavnensky horizon - a new stratone in the Lower Triassic of the East European platform - I. V. Novikov; V. P. Tverdokhlebov; V. R. Lozovsky (Известия высших учебных заведений: Геология и разведка)
A new horizon, called Zaplavnensky, is suggested on the base of verhnesukhorechenskaya subsuite of Buzulukskaya depression in the Lower Triassic of the East European platform. The horizon occupies an intermediate position between the Vokhminsky and the Rybinsky ones and is Dienerian (Late Induan) by age. The main characteristics of Zaplavnensky horizon are a specific pozdnesukhorechensky tetrapod assemblage described earlier as a special «Selenocara-Syrtosuchus fauna», as well as a reversal residual magnetization of the most of its strata.